2015
DOI: 10.1111/jvp.12199
|View full text |Cite
|
Sign up to set email alerts
|

Dosage assessment of valnemulin in pigs based on population pharmacokinetic and Monte Carlo simulation

Abstract: To estimate the valnemulin pharmacokinetic profile in a swine population and to assess a dosage regimen for increasing the likelihood of optimization. This study was, respectively, performed in 22 sows culled by p.o. administration and in 80 growing-finishing pigs by i.v. administration at a single dose of 10 mg/kg to develop a population pharmacokinetic model and Monte Carlo simulation. The relationships among the plasma concentration, dose, and time of valnemulin in pigs were illustrated as C(i,v) = X(0 )(8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…A short communication reported a bioavailability of 52.6% in broilers with no information on the fed or fasted status (Sun et al., 2017 ). In pigs, a study suggested a bioavailability of 59% but the confidence on this value is low due to the fact that the animals receiving treatment by oral and intravenous routes were not comparable (Yuan et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…A short communication reported a bioavailability of 52.6% in broilers with no information on the fed or fasted status (Sun et al., 2017 ). In pigs, a study suggested a bioavailability of 59% but the confidence on this value is low due to the fact that the animals receiving treatment by oral and intravenous routes were not comparable (Yuan et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This approach is widely used in human medicine (DeRyke, Kuti, & Nicolau, ; Frei, Wiederhold, & Burgess, ; Roberts, Kirkpatrick, & Lipman, ; Tanigawara, Nozawa, & Tsuda, ; Turnidge & Paterson, ; Zelenitsky, Ariano, Harding, & Forrest, ). A growing interest in population pharmacokinetics and MCS applied to the assessment of anti‐infectives dosage regimens was recently shown in veterinary medicine (Black, Landersdorfer, Bulitta, Griffith, & Govendir, ; Rey et al., ; Vilalta, Giboin, Schneider, El Garch, & Fraile, ; Yuan et al., ).…”
Section: Introductionmentioning
confidence: 99%